2021
DOI: 10.1002/jcp.30421
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of methylnaltrexone inhibits head and neck squamous cell carcinoma growth in vitro and in vivo by acting on the mu‐opioid receptor

Abstract: The Mu-opioid receptor (MOR) has been implicated in tumorigenesis and metastasis. Methylnaltrexone (MNTX), an antagonist of MOR, has shown to inhibit tumor growth and metastasis in lung cancer cell lines. The effect of MNTX on other cell lines such as head and neck squamous cell carcinoma (HNSCC) has not been investigated. We measured the expression and activity of the receptor in different HNSCC cell lines.Then, we evaluated the impact of modulating the expression MOR and the effect of MNTX on the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…In addition, the authors observed somewhat contrary results from the 3D cell culture model in which D,L-methadone could either enhance ovarian cancer cell proliferation or counteract the therapeutic effects of cisplatin (22). It is difficult to compare our results with these in vitro studies (18)(19)(20)(21). The possible reason to explain the discrepancy from in vitro studies is bias and confounding owing to unknown and unmeasured variables that might have an impact on the clinical survival outcomes (22)(23)(24).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…In addition, the authors observed somewhat contrary results from the 3D cell culture model in which D,L-methadone could either enhance ovarian cancer cell proliferation or counteract the therapeutic effects of cisplatin (22). It is difficult to compare our results with these in vitro studies (18)(19)(20)(21). The possible reason to explain the discrepancy from in vitro studies is bias and confounding owing to unknown and unmeasured variables that might have an impact on the clinical survival outcomes (22)(23)(24).…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, Gorur et al. observed that downregulating the MOR expression inhibited aggressive cell behaviors in squamous cell carcinoma of the head and neck ( 20 ). Fiegl et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Murine CT26 colon cancer cells Nalmefene was administered to cells in a concentration gradient (N1: 0.625 μg/l, N2: 0.25 μg/l, N3: 1 μg/l, and N4: 10 μg/l) for 10 h Nalmefene inhibited CT26 cell viability and migration in a concentration-dependent manner, also inhibited glycolysis of CT26 cells. The antitumor effect can be achieved through opioid receptor inhibition and downregulation of calmodulin expression and CaMK II phosphorylation, thus inhibiting the AKT-GSK-3β pathway and CT26 cell glycolysis Low doses of methylnaltrexone inhibits head and neck squamous cell carcinoma growth in vitro and in vivo by acting on the mu-opioid receptor [ 34 ]. Human HNSCC cell lines: FaDu (from the American Type Culture Collection), MDA686Tu and UMSCC47 (from the laboratory of Dr. Jeffrey N. Myers, The University of Texas M.D.…”
Section: Methodsmentioning
confidence: 99%
“…The literature suggests a cancer-promoting role for the μOR in both cancer and non-cancer cells that support tumour growth. The siRNA downregulation of μOR inhibited aggressive features in lung cancer and squamous cell carcinoma of the head and neck in vitro ( 21 , 34 , 36 ). Downregulation of μOR also decreased tumour take in the lungs after IV inoculation ( 21 ).…”
Section: Effect Of Opioid Receptor Manipulation On Tumour Growth and Aggressivenessmentioning
confidence: 99%